Antenna Design for the Localization of Pulmonary Lesions During Thoracoscopic Surgery. Issue 15 (2021) - Battistel, Alberto; Pott, Peter P.; Rößner, Eric D.; Möller, Knut
Abstract: Video-assisted thoracoscopic surgery (VATS) is the primary minimally invasive excise procedure for the diagnostics of pulmonary lesions. However, these lesions can be difficult to localize during the surgery as the lung collapses. Here we continue our study on the use of radio frequency technology directly during VATS as an intraoperative strategy for the location of pulmonary lesions. Finite Difference Time Domain (FDTD) simulations were used to compare a dipole and a bowtie antenna of different lengths. The results show that the bowtie antenna performs better than a dipole one, even if only marginally.